Risk Prediction in Medicine and Surgery: Ethical and Practical Considerations - Seymour, D. G. (J R Coll Physicians Lond, 1990)
Risk prediction is a subject of increasing clinical interest, and publications in this area are likely to have an important influence on patient care in the near future. A multiplicity of risk prediction systems, many of them computer-based, will raise a number of ethical and practical questions. These questions need to be addressed by the originators of systems, the editors of journals, practising clinicians, and the lay public.